Conservative surgical management of acquired uterine arteriovenous malformationassociated with unrecognized early miscarriage in a hemodynamicallyunstable patient: a case report - Saldaña Vargas, Roy Arnold (2026)
Acquired uterine arteriovenous malformation (UAVM) is an uncommon but potentially life-threatening cause of uterine bleeding following gestational events. Misdiagnosis may lead to inappropriate uterine evacuation procedures with a high risk of severe hemorrhage. We report the case of a 23-year-old woman with no prior diagnosis of pregnancy who presented with self-limited heavy vaginal bleeding. Serum β-hCG levels were mildly elevated (7.3 mIU/mL, decreasing to 6 mIU/mL). Transvaginal Doppler ultrasound revealed a hypervascular myometrial lesion measuring 35 × 30 mm, with a peak systolic velocity of 70 cm/s and a resistance index of 0.22, without evidence of retained products of conception. Computed tomography angiography confirmed an arteriovenous communication originating from the right uterine artery. During hospitalization, the patient developed acute hemodynamic deterioration (shock index 1.4), requiring blood transfusion and emergency conservative surgical management. The procedure included temporary bilateral uterine artery occlusion, local hemostatic infiltration, and wedge resection of the vascular nidus with uterine reconstruction. At 3-month follow-up, complete resolution was observed, with restoration of regular menstrual cycles and no residual arteriovenous shunting. In hemodynamically unstable patients, surgical resection with temporary vascular control may represent an effective fertility-preserving alternative when immediate embolization is not feasible, allowing definitive hemorrhage control.